2009
DOI: 10.1021/ol9023369
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Allylic C−H Acetoxylation and Benzoyloxylation via Suggested (η3-Allyl)palladium(IV) Intermediates

Abstract: Palladium-catalyzed allylic acetoxylations and benzoyloxylations were carried out using iodonium salts. The reactions proceed under mild conditions with high regio- and stereoselectivity. The catalysis can be performed under both acidic and nonacidic conditions without use of BQ or other external oxidants and activator ligands. Deuterium labeling experiments clearly show that the catalytic reaction proceeds through (eta(3)-allyl)palladium intermediates. A stoichiometric study with one of the catalysts provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(57 citation statements)
references
References 32 publications
1
56
0
Order By: Relevance
“…In order to understand the transfer of Cl + from LPd IV Cl 4 to π-systems, we studied the reaction of 7 and 7·Cl − with alkenes in more detail. Interactions of isolated Pd IV -compounds with alkenes or alkynes have never been studied, even though the existence of (η 2 -alkene/alkyne)Pd IV -complexes was proposed in Heck-reactions 42, 66 and other carbopalladations, 67 allylic C-H acetoxylations 68 , and cyclotrimerisations. 69 …”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the transfer of Cl + from LPd IV Cl 4 to π-systems, we studied the reaction of 7 and 7·Cl − with alkenes in more detail. Interactions of isolated Pd IV -compounds with alkenes or alkynes have never been studied, even though the existence of (η 2 -alkene/alkyne)Pd IV -complexes was proposed in Heck-reactions 42, 66 and other carbopalladations, 67 allylic C-H acetoxylations 68 , and cyclotrimerisations. 69 …”
Section: Discussionmentioning
confidence: 99%
“…28,30 For allylic C−H oxidation, White and coworkers have suggested that a carboxylate counterion on palladium is needed to effect C−H cleavage. 31 A carboxylate anion also plays a key role in the C−H activation step of the proposed Pd(II)/Pd(IV) catalytic cycle for an allylic C−H acetoxylation 32 or as a base in a recently published allylic acyloxylation. 33 Similarly, for allylic aminations, a carboxylate anion has also been suggested to be involved in the cleavage of the C−H bond.…”
Section: ■ Computational Studymentioning
confidence: 99%
“…Pd(OAc) 2 is one of the most common commercially available Pd II sources and, therefore, is the most prevalent Pd source for allylic oxidation, among other reactions . Szabó and co‐workers reported two strategies for acyloxylation catalyzed by Pd(OAc) 2 : (a) using 4 equivalents of carboxylic anhydride or (b) incorporating the carboxylate source into their oxidant by utilizing 3–3.5 equivalents of a hypervalent iodine oxidant with the corresponding lithium carboxylate salt . Hartwig and co‐workers used stoichiometric tert ‐butylbenzoyl peroxide and Pd II benzoate to form allyl benzoates, reducing carboxylate loading to 2 equivalents .…”
Section: Methodsmentioning
confidence: 99%